RETHINKING THE PUBLICATION OF NAMES AND PHOTOGRAPH OF CYBERCRIME SUSPECTS IN CYBERSPACE IN NIGERIA: LESSONS FROM THE USA AND SOUTH AFRICA. - Eboibi, Felix E.; Richards, Newman U. (LexScriptio A Journal of the Department of Jurisprudence and Public Law, 2025)
The increase in the commission of cybercrimes, especially internet fraud, at the domestic and international levels, has put Nigerian cybercrime investigators in the global searchlight. This is arguably due to questions of competency and efficiency in enforcing the implementation of cybercrime legal frameworks and curtailing the upsurge of cybercrimes by Nigerians. Oftentimes, cybercrime investigators, after the apprehension of cybercrime suspects, resort to displaying their names and photographs in cyberspace before the conclusion of an investigation. While drawing lessons from the USA and South Africa, this paper argues that this act of the cybercrime investigators is a cyberspace parade and trial, which is unlawful and a breach of the fundamental human rights of cybercrime suspects. The aim of this paper is to evaluate the legal implications of cyberspace parade and trial in Nigeria and the main objective is to demonstrate that cyberspace parade and trial is unlawful. This paper adopts the doctrinal research design and data is sourced from primary and secondary sources. The paper found that the practice of cyberspace parade and trial is unlawful and unconstitutional. Considering the foregoing, it is recommended that a federal law banning cyberspace parades and trials should be enacted.